Impact of Hormones on the Proliferation of Shoots and Initiation of Roots in Salvia santolinifolia (Boiss), A High Value Medicinal Herb: Impact of Hormones on Shoots - Jan, Tour; Naqvi, Beena; Hazrat, Ali; Qadri, Raiha; Nisar, Muhammad; Khan, Nasrullah; Nawaz, Muhammad Asif; Pervez, Sidra (Biological Sciences - PJSIR, 2020)
Salvia santolinifolia is a medicinal plant and an efficient in vitro conservation system is established. The influence of N6Benzylaminopurine (BAP), N6-(2-isopentyl)-adenine (2iP) and Kinetin at various concentrations were evaluated, single and in mixture with NAA (Naphthalene acetic acid) for the production of auxiliary shoots from nodal explants of S. santolinifolia. BAP at 3.0 mg/L in MS1 media produced maximum (11.66±3.38) number of shoots while elongated (5.37±1.45) shoots were produced in the MS2 medium in subcultures at 2.0 mg/L of 2iP. Least number of shoots were formed when auxin and cytokinin were used in combination. Length of culture, age was an important consideration for the initiation and development of roots. Rooting of shoot was attained with Indol-3-butyric acid (IBA) (3.0 mg/L) from shoots of 4th, 5th and 6th subculture while shoots taken from 1st, 2nd and 3rd subculture failed to form roots.